Intercultural communication and conflict management among Malaysian employers and Indonesian domestic workers in Kuala Lumpur - Lukman, Inon Beydha; Othman, Jamilah; Hassan, Md. Salleh; Sulaiman, Abdul Hadi (Universiti Putra Malaysia, 2009)
This paper aims to investigate sources of conflict in communication at the domestic workplace among Malaysian employers and Indonesian domestic workers in Kuala Lumpur. The following questions will be addressed: what patterns and context of communication do they use, what strategies do they use in managing with these conflicts? The data collection methods included both descriptive quantitative and qualitative that consisted of a survey questionnaire, open-ended guided interviews, and a review of the relevant literature. Data were collected from the 110 Malaysian employers and 110 Indonesian domestic workers in Kuala Lumpur who filled out the survey in January 2009. The findings indicate that: 1) conflicts in communication at domestic workplace among participants arose out of culturally-based differences in context and pattern of communication, difference assumptions about verbal and non-verbal or direct and indirect communication styles, and differences strategy in manage these conflict 2) The Malaysian employers tended to use either a dominating style or an integrating style in dealing with conflict, and 3) The Indonesian domestic workers tended to use either a avoiding style or integrating style in dealing with conflict. Finally, this study makes recommendations as how to better prepare Indonesian domestic workers working with Malaysian employers at domestic workplace in Malaysia and other Indonesian domestic workers working in intercultural or international domestic workplace, to resolve culturally-based interpersonal conflicts more effectively.